HUBUNGAN PERAN INTERAKSI AYAH DAN ANAK USIA 4-5 TAHUN DENGAN KEDISIPLINAN DI TK DESA PEMATANG KECAMATAN BATANG PERANAP KABUPATEN INDRAGIRI HULU - Fitri Fitri; Zulkifli Zulkifli; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was motivated by the low level of discipline inkindergartens in Pematang Village, BatangPeranapSubdistrict, Indragiri Hulu Regency, which is related to the role of father and child interaction.This study aims to determine the relationship between the role of interaction between father and child aged 4-5 years with discipline, in Pematang Village Kindergarten ofBatangPeranap District, Indragiri Hulu Regency.The type of this research is correlation with quantitative methods. Data collection techniques used were observation sheets and questionnaires. The population was 30 children and 30 parents. Based on the results of calculations using the Chi Square formula, the samples set in this study were 30 children and 30 parents. The sampling technique used in this study was saturated sampling. Data analysis technique uses correlation test from Chi Square with IBM SPSS Ver.22 program. Based on the results of hypothesis testing obtained there is apositive and significant relationship between the role of interaction between father andchild aged 4-5 years with discipline in the Pematang Village Kindergarten inBatangPeranap District, Indragiri Hulu Regency. It can be seen that the results of the Chi Square formula obtained a value of 10,556 with a probability of 0.023. Obtained a value of df = 2 at alpha 5% of 5.991. Then it is known that chi square counts (10,556)>(5,991) or probability (0,032) <0,05. This means that there is a relationship betweenthe role of father and child with discipline.Key Words: The role of father and child, discipline